Perluasan Teori Maqashid Al-Syariâ€™ah: Kaji Ulang Wacana Hifdz Al-â€˜Ummah A. Djuzuli - Dedi, Syahrial (Al-Istinbath: Jurnal Hukum Islam, 2016)
This paper wasdone the discourse of â€œhifdz al-'ummah/the savior of nationâ€ of A. Djazuli in the theory of â€œmaqashid al-shari'ahâ€. Because the benefit is the essence or substance of Islamic law.Mentioning the essence or substance of Islamic law intended to mean that the beneficiaries are a key element of the building of Islamic law, which binds other related ones. The data presented in this paper comes from primary sources directly related to A. Djazuli thought. This study found that the study of â€œmaqashid al-shari'ah/the purpose of lawâ€ which is now developing emphasize to people as individual and less offset by humans as members of the community. The concept of people becomes important in life togetherwhether people within the scope of the first, second, or third which are well aligned with the economic, political, and social-culture aspects of a nation or the international community. In the era of globalization, the roles of aspects become very strong and their interaction becomes very intensive.